The Implementation of Cooperative Learning Model in Indonesian Language Learning in Grade IV of Madrasah Ibtidaiyah Jayapura City - Mukti, Fajar Dwi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This study evaluates implementing the Cooperative Learning learning model in Indonesian language learning in grade IV MIN Jayapura City. The research method used was graderoom action research consisting of two cycles. Each cycle includes planning, action, observation, and reflection stages. The research subjects were students of grade IV MIN Jayapura City. Data collection was carried out using observation techniques. The study results show that applying the cooperative learning model in learning Indonesian can increase students' creativity in learning. This increase can be seen from the results of observations, which showed a boost from the first cycle of 75.72% to 85.72% in the second cycle. Based on these data, it can be concluded that the implementation of the Cooperative Learning learning model in Indonesian language learning in grade IV MIN Jayapura City can increase student creativity in learning, as well as provide a more positive learning experience for students.